Identification of NF‐κB inhibitors in Qishenyiqi dropping pills for myocardial infarction treatment based on bioactivity‐integrated UPLC‐Q/TOF MS. (6th April 2015) - Han, Yanqi; Zhou, Mengge; Xing, Lu; Jiang, Min; Bai, Gang; Luo, Guoan
Abstract Qishenyiqi dropping pills (QSYQ) are a type of standardized cardiovascular multiherb medicine for the treatment of myocardial infarction (MI). Knowledge concerning the systemic identification of nuclear factor‐kappa B (NF‐κB) inhibitors of QSYQ is generally lacking. Therefore, it is necessary to establish an effective method to screen the bioactive components of NF‐κB inhibition. In the present study, a rat model of coronary artery ligation was used to assess the cardioprotective effects of QSYQ. The electrocardiograms, histopathology of heart tissues and serum biochemical indicators, such as brain natriuretic peptide, cardiac troponin I and inflammatory cytokines, were measured. Subsequently, ultra‐performance liquid chromatography quadrupole/time‐of‐flight mass spectrometry (UPLC‐Q/TOF MS) combined with the NF‐κB luciferase reporter assay system was applied to screen the potential anti‐inflammatory compounds in QSYQ. The results revealed that the administration of QSYQ could improve heart function, ameliorate neutrophil infiltration and diminish the levels of inflammatory cytokines in MI rats. Furthermore, 22 compounds were determined to be potential NF‐κB inhibitors. In conclusion, NF‐κB inactivation and cytokine suppression might be the main mechanisms of QSYQ for MI treatment. The method of UPLC‐Q/TOF MS combined with a bioactive human cell functional evaluation system was proved to be a simple and effective strategy for screening bioactive compounds in traditional Chinese medicine prescriptions. Copyright © 2015 John Wiley & Sons, Ltd.